Blood Glucose Levels in Patients with Coronary Artery Disease - Rajbhandari, Ajay; Pandeya, Dipendra Raj; Bhattarai, Madhur Dev; Malla, Ravi (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Diabetes Mellitus is a potent risk factor for Coronary Artery Diseases, but Impaired Glucose Tolerance is increasingly known risk factor for Coronary Artery Diseases. The aim of this study was to correlate blood glucose level in the patients with Coronary Artery Diseases with Acute Coronary Syndrome and to determine the relati onship of other risk factors. Methods: This was a cross-secti onal prospecti ve study of consecutive patients admitted in coronary care unit of Bir Hospital and Shaid Gangalal National Heart Center, with diagnosis of Acute Coronary Syndrome. Results: Total 209 patients were enrolled. 90.9% (190) had dyslipidemia, 78.5% were smokers with mean Standard Deviation of duration of smoking were 25.35 years. Abnormal waist to hip ratio in male and female are 56.3% and 76.1% respectively. 14.4 % (30) had Random Blood Glucose > 200mg%, 17.2 % had Impaired Fasting Glucose (110-126 mg% World Health Organizati on); 34.4% had Impaired Fasting Glucose (100-126 mg% American Diabeti c Associati on) 28.2% had Impaired Glucose Tolerance (postprandial blood glucose 140-200mg %).19.1% were old diabetes, 21.3% had recent diabetes mellitus, 52.7% had impaired glycemia.93.1% of total patients had Glucose Intolerance of any form. Conclusions: Almost all patients had diabetic or glucose intolerance of any form prior to coronary artery disease with acute coronary syndrome. This study consisted with Asian criteria of body mass index and Waist circumference for overweight or obesity. Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/4-8 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7758